Dynamics of Dissolved Organic Carbon and Methane Emissions in a Flooded Rice Soil - Lu, Yahai; Wassmann, Reiner; Neue, Heinz-Ulrich; Huang, Changyong (Soil Science Society of America journal, 2000)
Limited information is available on the dynamics of dissolved organic C (DOC) and its relationship with CH4 emissions in flooded rice (Oryza sativa L.) soils as affected by rice cultivar. Greenhouse and laboratory experiments were conducted to determine root C release in culture solution, DOC and dissolved CH4 concentration in soil solution, and CH4 emission in a flooded soil planted with three rice cultivars. Soil solutions were sampled in the root zone (soil surrounding rice roots) and the non‐root zone (soil outside the root zone). The release of root exudates increased in the order: IR65598 (new plant type) < IR72 (modern cultivar) < Dular (a traditional cultivar). Correspondingly, DOC concentrations in the root zone and CH4 emission rates increased. The dynamics of DOC and dissolved CH4 differed greatly between the root zone and the non‐root zone. Dissolved organic C in the root zone increased with plant growth and reached maximum (13–24 mmol C L−1) between rice flowering and maturation (Week 11–13), whereas DOC in the non‐root zone remained low (1–5 mmol C L−1) throughout the growing season. Similarly, dissolved CH4 concentrations in the root zone increased sooner and were greater (mean 138 μmol CH4 L−1) than those in the non‐root zone (mean 97 μmol CH4 L−1). The seasonal patterns of CH4 emissions closely followed the dynamics of DOC concentrations in the root zone. The results suggest that (i) DOC pool in the root zone of rice plants is enriched by root‐derived C; (ii) the rates of CH4 emissions are positively correlated with the dynamics of DOC in the root zone; (iii) the intercultivar difference in root C releases is responsible for the intercultivar difference in DOC production, and consequently in CH4 flux.